Religious conversion, philosophy, and social science - Spinney, Oliver Thomas (International journal for philosophy of religion, 2023)
I argue that empirical studies into the phenomenon of religious conversion suffer from conceptual unclarity owing to an absence of philosophical contributions. I examine the relationship between definition and empirical result in the social sciences, and I show that a wide divergence in conceptual approach threatens to undermine the possibility of useful comparative study. I stake out a distinctive role for philosophical treatments of studies into religious conversion. I conclude with the suggestion that use of the terms ‘convert’ and ‘conversion’ may not in fact be conducive to clarity in the present context, and that subsequent studies may improve their precision through replacing them.